RASIO FREKUENSI PAKAN ALAMI Tubifex UNTUK SUBSTITUSI Artemia PADA BERBAGAI KELAS UKURAN BENIH IKAN BOTIA (Chromobotia macracanthus Bleeker) - Rina Hirnawati Hirnawati; Nina Meilisza; Sulasy Rohmy; Agus Priyadi (Journal of Fish Nutrition, 2021)
Artemia is the main feed in botia seeds up to three months of age so artemia substitution is essential for efficient maintenance. The study aimed to determine tubifex frequency ratio to substitute Artemia in botia seeds. The botia seeds used are one month old with a weight of 35-90 mg and a length of 13-20 mm are maintained in the recirculation system for eight weeks to three months of age. The study design is a complete randomized design (RAL) factor of two factors, namely the first factor is the class of fish size S (35-54 mg), M (55-74 mg), L (75-94 mg) and the second factor in the form of five ratios of artemia substitution frequency: Tubifex from A (4:0) which is 4 times a day for Artemia and 0 times a day for Tubifex, B (3:1), C (2:2), D (1:3) and E (0:4). Fifteen interaction treatments result from both factors namely SA (size S; frequency ratio A), SB, SC, SD, SE, MA, MB, MC, MD, ME, LA, LB, LC, LD, and LE repeated twice. Observations are made by measuring growth i.e. weight, total length, and sintasan. Data analyzed statistics followed by the Tukey test. The results showed that Tubifex can be given as many as 4 times per day across all fish size classes without artemia.